Gender Role Orientation and Marriage Adjustment as Factors Affecting Gender Role Conflict of Pastors’ Husbands - Karina Meriem Beru Brahmana (Journal of Educational, Health and Community Psychology, 2020)
The purpose of this research is to determine the effect of gender role orientation and marriage adjustment on the emergence of gender role conflict of pastors’ husbands. This research uses a non-experimental quantitative research method and is analyzed using SEM-PLS (Structural Equation Model-Partial Least Squares). This study uses three scales, namely The Gender-role Conflict Scale developed by O'Neil., et al (1986) to measure gender role conflict, Sex Role Orientation Inventory (SROI) developed by Tomeh (1978) to measure orientation of gender roles, and The Dyadic Adjustment Scale (DAS) from Spanier (1976) used to measure marriage adjustment. The subjects in this research are husbands of GBKP pastors totaling 79 people. Based on the hypothesis testing, it is revealed that marital adjustment influences gender role conflict in pastors’ husbands, whereas gender role orientation does not affect the pastor husband's gender role conflict. Researchers who are interested in examining gender role conflicts in men are expected to be able to include other variables that have not been studied in this research, such as spirituality, religiosity, coping strategies, cultural influences, etc., in order to enrich and develop the science of psychology, especially social psychology.